Influência da inflamação crônica de baixo grau na susceptibilidade à tuberculose e resposta vacinal em camundongos - Resende, Danilo Pires de (2019)
Chronic conditions associated with inflammation, such as obesity (OB), diabetes mellitus (DM) and tuberculosis (TB), are serious public health problems. The OB epidemic is increasing worldwide; and the prevalence of adult obesity nearly doubled between 1980 and 2017. Since DM is associated with diabetes, the prevalence of diabetes also increased over the same period, reaching 9% of the adult population worldwide, totaling 422 million people. Studies have been demonstrating DM as a risk factor for the development of tuberculosis, raising the hypothesis of an association between OB, DM and TB. Circulating monocyte subpopulation proportions have been shown to change during OB, DM, and TB, however no studies have evaluated monocyte subpopulations in severe OB / DM and if there are characteristics that may be associated with increased susceptibility to TB. In the first part of this study we demonstrated, in a cross-sectional study, with individuals with severe OB (BMI over 35kg / m2) with or without OB (DM) (n = 50 individuals per group) that the population did not of monocytes from OBDM individuals presents similar characteristics to monocytes from individuals with active pulmonary TB, and monocytes from OBDM and TB individuals are more susceptible to Mycobacterium tuberculosis (Mtb) infection. This suggests that phenotypic similarity and susceptibility of monocytes may be factors contributing to the association between tuberculosis and obesity. Since monocytes/macrophages change in obesity and these changes interfere with the ability to control Mtb, we decided to assess whether the development of obesity could alter the ability to rescue the specific immune response following M. bovis BCG vaccination. Thus, in the second part of this paper, we evaluated whether obesity interferes with BCG vaccine response by vaccinating young C57BL / 6 mice and inducing obesity by hypercaloric diet and by analyzing the immune response after Mtb challenge. Obesity induced after BCG vaccination did not interfere with TCD4 + IFNγ + lymphocyte rescue after Mtb challenge. However, this response to Mtb has been reduced. These results suggest that vaccination of non-obese animals induces vaccine immune responses that do not change with obesity induced metabolic changes.